Zooarchaeological evidence that the brown mussel (Perna perna) is a bioinvader of coastal Brazil. (November 2018) - Silva, Edson P; Souza, Rosa CCL; Lima, Tania A; Fernandes, Flávio C; Macario, Kita D; Netto, Bruna M; Alves, Eduardo Q; Carvalho, Carla; Aguilera, Orangel; Duarte, Michelle R
Interactions between invader species and the local biota may lead to disequilibria in regional ecosystems. For such reason, the cultivation of nonnative species may be prohibited in specific regions, as a means of protecting native species. On the other hand, the question of whether a species is a bioinvader or not may not be straightforward. This is the case of the mollusc Perna perna, presently naturalized and widely distributed along Brazilian coast, from the Bay of Vitória, in the state of Espírito Santo (ES), to the state of Rio Grande do Sul (RS). Following previous works that explored the hypothesis that P. perna invaded the coast of Brazil at the colonial period, attached to slave ships, we discuss zooarchaeological data, radiocarbon dating, and molecular genetics analyses. Out of the 578 archeological shellmounds investigated, 542 (93.8%) had no records of P. perna . From the radiocarbon dating results, it is possible to infer that the presence of the two P. perna specimens from the Saquarema shellmound, in Rio de Janeiro, as well as the other shells from the top layer, is likely related to a recent occupation of the site in the colonial period, with a great probability of being from the XVII or XVIII centuries. Data on genetic population structure of P. perna along the Brazilian coast showed higher genetic identities between the African and the Brazilian populations than among the Brazilian populations, while haplotypic diversity shows a pattern which relates to trade routes of slaves (XVII and XVIII centuries) between Africa and Brazil. These data reinforce the argument that the appearance of P. perna along the Brazilian coast is due to invasion during historical time.